Bewertung der Energieeffizienz von Antriebssystemen mobiler Arbeitsmaschinen am Beispiel Bagger - Sturm, Christoph (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2015)
In this book a methodology for the evaluation of energy efficiency of mobile working machines by simulation is presented. It allows an efficiency analysis and systematic optimization of a single power train as well as a comparison of different power train concepts. The methodology is applied to a wheeled excavator. To ensure a realistic power demand in the simulation, a rule-based operator model is developed.